2010
DOI: 10.4172/2157-7560.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Review of Gardasil

Abstract: Human papillomavirus (HPV) is necessary for the development of cervical cancer. Cervical cancer is the second most common cancer in women worldwide but 80% occurs in developing countries, not countries with Pap screening programs. Pap screening programs in industrialized countries have reduced the incidence of cervical cancer to 4–8/100,000 women. HPV vaccines may be a promising strategy for cervical cancer in women without access to screening programs. In industrialized countries, the benefit of HPV vaccines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
0
22
0
3
Order By: Relevance
“…In general, vaccine is designated to prevent against infectious diseases. To prevent HPV infection, two prophylactic vaccines have been developed; a quadrivalent vaccine (Gardasil ® ; Merck & Co., USA) against L1-like virus particles to HPV types 6, 11, 16 and 185, and a bivalent HPV vaccine (Cervarix ® ; Glaxo Smith Kline, London) against types 16 and 18, which are thought to be the most frequent of the 15 types associated with cervical cancer. Clinical trials revealed both Gardasil and Cervarix to be safe and effective against cervical cancer6; thus, the two vaccines were introduced for administration in 2006 with approximately 175 million doses being distributed worldwide since then.…”
mentioning
confidence: 99%
“…In general, vaccine is designated to prevent against infectious diseases. To prevent HPV infection, two prophylactic vaccines have been developed; a quadrivalent vaccine (Gardasil ® ; Merck & Co., USA) against L1-like virus particles to HPV types 6, 11, 16 and 185, and a bivalent HPV vaccine (Cervarix ® ; Glaxo Smith Kline, London) against types 16 and 18, which are thought to be the most frequent of the 15 types associated with cervical cancer. Clinical trials revealed both Gardasil and Cervarix to be safe and effective against cervical cancer6; thus, the two vaccines were introduced for administration in 2006 with approximately 175 million doses being distributed worldwide since then.…”
mentioning
confidence: 99%
“…La controversia en torno a la efectividad y seguridad de las vacunas para la prevención de la infección por VPH Los informes de casos por parte de investigadores independientes dan cuenta de estos y otros posibles efectos adversos relacionados con la vacuna tetravalente contra VPH. Si bien los informes aislados de casos no constituyen la mejor evidencia en cuanto a la seguridad de la vacuna, su importancia no se puede subestimar y son necesarios más estudios poscomercialización y de farmacovigilancia que permitan establecer nexos reales de causalidad entre los eventos reportados y la aplicación de la vacuna (14). Se han informado casos de síndrome ASIA (síndrome autoinmune/ inflamatorio inducido por adyuvante) relacionados con la aplicación de la vacuna contra el VPH, así como cuadros de disautonomía, actualmente en investigación.…”
Section: Resultsunclassified
“…La vacuna tetravalente ofrece un perfil similar en cuanto a la reducción de NIE grados 2 y 3 a mujeres que acceden a estrategias de cribado, así como un 10% en reducción de citologías normales, un 20% en la disminución de colposcopias y un 42% en la realización de tratamientos. Pero la incidencia de CCU entre mujeres con acceso a CCV, más aplicación de vacuna tetravalente, no es menor que la incidencia en mujeres con acceso a CCV sin vacunación (14).…”
Section: Vacunas Contra El Vph Costo-efectividad Y Salud Públicaunclassified
“…Previous data have showed that Gardasil Ò coadministered with Menactra TM (meningococcal vaccine) or Adacel TM (tetanus toxoid, reduced diphtheria toxoid and acellular pertussis vaccine) was well tolerated and did not interfere with the immune response to the respective vaccines. [69][70][71][72] Both clinical studies (Studies V503-005 and V503-007) evaluated the tolerability and immunogenicity of administration of the first 9vHPV vaccine dose at the same time as Menactra TM and Adacel TM vs. administration of the 9vHPV vaccine one month before the administration of Menactra TM and Adacel TM in adolescents aged 9-14 y. [73][74][75][76] The result demonstrated that both safety and the immune response to all components of the administered vaccines were non-inferior compared with nonconcomitant administration (Table 1S).…”
Section: Concomitant Administration With Other Vaccinesmentioning
confidence: 99%